SOIL SOLAR-WARMING WITH DIFFERENT TYPES OF MULCH - S.A. Gaafer Salman, S.R.;; Mettawee E.S. (Arab Universities Journal of Agricultural Sciences, 2005)
temperature was studied during two successive seasons of 2002 and 2003 at Kaha experimental station, Agricultural Research Center, Cairo, Egypt (Latitude, longitude, and altitude are 30.8, 31.15, and 16.9 m respectively). Cucumber seedlings (Cucumis sativus L. F1 local hybrid Sinai 1) were grown in clay soil under unheated two plastic houses. One of them was covered with one year old cladding material (PE 200μm) while the other was covered with new cladding. Soil surface was covered with different plastic mulch colors, i.e., black, silver, and transparent, in addition to a new suggested mulch that was craft-paper saturated with paraffin wax. Soil temperatures were measured at 5 cm depth. Global solar radiation and air temperature were measured inside and outside the greenhouses. The vegetative growth , i.e., plant height, leaf number, leaf fresh and dry weight, early and total yield were recorded. The results showed that new cladding cover promoted plant growth and yield. Craft-paper saturated with paraffin wax gave the highest soil temperature during the sunny days in comparison with other mulches and best results concerning vegetative growth and yield were obtained by both black mulch and craft-paper saturated with paraffin